LTP syndrome and edible insect allergy in a patient with recurrent anaphylaxis incidents - Jankowski, Wojciech; Przychodniak, Dominik; Kurowski, Marcin (Alergologia Polska - Polish Journal of Allergology, 2025)
An increase in the consumption of imported plant products, among other dietary changes, can result in elevated exposure to non-specific lipid transfer proteins (nsLTPs), which may trigger allergic reactions designated as lipid transfer protein (LTP) syndrome. Currently, edible insects are being incorporated into the diet as an alternative source of protein. Despite the advantages they offer, they pose a potential risk of allergic reactions. This case report presents a 66-year-old patient with recurrent anaphylaxis episodes, and IgE-sensitization to multiple nsLTPs and to proteins of edible insects ( Acheta domesticus, Locusta migratoria, Tenebrio molitor ). It emphasizes the necessity of consumer education and accurate labelling of food products containing edible insects and plants with nsLTPs. Such measures can help reduce the risk of allergic reactions, both primary and cross-reactive ones. Additionally, this case illustrates the potential of the ALEX2 Multiplex test as an effective method for identifying sensitization to multiple allergens.